Identification of a novel umami peptide in tempeh (Indonesian fermented soybean) and its binding mechanism to the umami receptor T1R. (15th December 2020) - Amin, Muhamad Nur Ghoyatul; Kusnadi, Joni; Hsu, Jue-Liang; Doerksen, Robert J.; Huang, Tzou-Chi
Highlights: Tempeh is a popular Indonesian fermented soybean with umami taste. GK 15, a < 3 kDa peptide, was found to be a source of umami taste in tempeh. ESI-LC-MS/MS was a fast method for novel peptide identification. ZDOCK was a robust method to analyze the binding mechanism of GK-15 into T1R3. Abstract: Tempeh, a traditional Indonesian soybean product produced by fermentation, is especially popular because of its umami taste. In this study, a novel umami peptide GENEEEDSGAIVTVK (GK-15) was identified in the small peptide (<3 kDa) fraction of the water extract of tempeh using LC-MS/MS analysis and database-assisted identification. The umami taste of GK-15 was further validated using sensory evaluation, which suggested that GK-15 may be one of the key components contributing to the umami taste in tempeh. To rationalize the biological effect of GK-15, molecular docking of GK-15 into the N -terminal extracellular ligand-binding domain of the umami (T1R) receptor was performed. ZDOCK data showed that GK-15 could perfectly bind either to the open or closed conformation of T1R3. To the best of our knowledge, the present work is the first study to focus on the screening of umami peptides from tempeh.